LEGAL PROTECTION ASPECT OF SELLING DRUG TRANSACTIONS THROUGH ONLINE PHARMACY SERVICE - Mutiara, Upik; Insani, Nur (Legal Standing : Jurnal Ilmu Hukum, 2020)
This writing aims to find out how the form of legal protection against consumers in the event of default in conducting drug sales transactions through online pharmacy services and to find out the form of liability by the seller or pharmacist when committing negligence to consumers in the transaction. This writing uses the normative legal research method with the data collection method used is the Literature Method; Tracing the research material is done by reading, studying, and quoting legislation, and related literature and then the data obtained are analyzed qualitatively.The results of this study address that: (1) the form of legal protection for online pharmacy consumers has been specifically regulated in the health law, the law on health workers and generally regulated in the consumer protection law. (2) The legal consequences obtained by the pharmacist or negligent seller is to provide compensation to consumers if proven to have neglected and are responsible for their profession both in civil and administrative terms. Based on these results, it is recommended: (1) pharmacists or sellers to pay close attention to every doctor's prescription that enters the pharmacy system in order tomaintain the safety and security of consumers in consuming drugs. (2) Consumers or the public must be more careful when receiving drugs from pharmacists so that if pharmacists are negligent, drugs can be replaced immediately before consumption.